Publisher Correction: Identification of cell surface markers and establishment of monolayer differentiation to retinal pigment epithelial cells - Alvaro Plaza Reyes (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.